2018
DOI: 10.1053/j.gastro.2017.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Epigenomic Aberrations in Esophageal Squamous Cell Carcinoma and Implications for Patients

Abstract: Esophageal squamous cell carcinoma (ESCC) is a common malignancy without effective therapy. The exomes of more than 600 ESCCs have been sequenced in the past 4 years, and numerous key aberrations have been identified. Recently, researchers reported both inter- and intratumor heterogeneity. Although these are interesting observations, their clinical implications are unclear due to the limited number of samples profiled. Epigenomic alterations, such as changes in DNA methylation, histone acetylation, and RNA edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
155
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(156 citation statements)
references
References 142 publications
(137 reference statements)
1
155
0
Order By: Relevance
“…ESCC is common (more than 400,000 cases each year) and aggressive malignancy (causing almost 300,000 deaths per year), with a 5-year survival rate less than 20% Enzinger and Mayer, 2003). Unfortunately, genome-guided therapeutic strategy is still unavailable for ESCC patients, although ESCC genomic abnormalities have been comprehensively characterized and established (Cancer Genome Atlas Research et al, 2017;Gao et al, 2014;Lin et al, 2018a;Lin et al, 2014;Lin et al, 2018b;Liu et al, 2017;Song et al, 2014). In addition, the high-degree genomic heterogeneity of this cancer further limits application of mutational-targeted therapy.…”
mentioning
confidence: 99%
“…ESCC is common (more than 400,000 cases each year) and aggressive malignancy (causing almost 300,000 deaths per year), with a 5-year survival rate less than 20% Enzinger and Mayer, 2003). Unfortunately, genome-guided therapeutic strategy is still unavailable for ESCC patients, although ESCC genomic abnormalities have been comprehensively characterized and established (Cancer Genome Atlas Research et al, 2017;Gao et al, 2014;Lin et al, 2018a;Lin et al, 2014;Lin et al, 2018b;Liu et al, 2017;Song et al, 2014). In addition, the high-degree genomic heterogeneity of this cancer further limits application of mutational-targeted therapy.…”
mentioning
confidence: 99%
“…A recent review article highlighted WES of ESCCs that revealed many crucial driver mutations and also mentioned WES for elucidating inter‐ and intratumor heterogeneity. This article also discusses the epigenetic alterations in ESCC emphasizing a major challenge of understanding epigenetic mechanisms contributing to carcinogenesis . A couple of studies summarized and re‐analyzed the genomic data from several recent genomic studies of large cohorts of ESCC patients .…”
Section: Genomics Mutations and Deregulated Pathwaysmentioning
confidence: 99%
“…This article also discusses the epigenetic alterations in ESCC emphasizing a major challenge of understanding epigenetic mechanisms contributing to carcinogenesis. 31 A couple of studies summarized and re-analyzed the genomic data from several recent genomic studies of large cohorts of ESCC patients. 32,33 The re-analysis by Du et al identified recurrent mutations in approximately 18 genes, 15 of which had been reported previously (TP53, AJUBA, CDKN2A, KMT2D (MLL2), ZNF750, FAT1, NOTCH1, NOTCH3, PIK3CA, NFE2L2, RB1, KDM6A, FBXW7, CREBBP, and TGFBR2), with three significantly mutated novel genes (CUL3, PTEN, and DCDC1).…”
Section: Genomics Mutations and Deregulated Pathwaysmentioning
confidence: 99%
“…Alcohol intake and tobacco use are responsible for at least 75% of these carcinomas. The underlying initiation and progression mechanisms of OSCC and ESCC are generally characterized by the accumulation of serial epigenetic and genetic alterations, which eventually lead to uncontrolled proliferation of the mutated cells, followed by vigorous cell division . Early‐stage OSCC detection displays an 80% survival rate at 5 years, while detection at advanced stage leads to survival rates ranging from 20% to 40% .…”
Section: Introductionmentioning
confidence: 99%